2022
DOI: 10.3390/nu14102055
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Copper and Selenium Intakes and the Risk of Type 2 Diabetes Mellitus: Findings from the China Health and Nutrition Survey

Abstract: The long-term associations between dietary copper (Cu) and selenium (Se) intakes and type 2 diabetes mellitus (T2DM) risk are unclear. We aimed to examine the prospective associations between dietary Cu and Se intakes and T2DM risk in Chinese adults. A total of 14,711 adults from the China Health and Nutrition Survey (1997–2015) were included. Nutrient intakes were assessed by 3 consecutive 24 h recalls and food-weighing methods. T2DM was identified by a validated questionnaire and laboratory examination. Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…The higher dietary copper intake may be related to the different dietary habits of adults in Western countries and China. Chinese Accepted manuscript diets tend to include large amounts of grains and legumes (26) , which are major sources of dietary copper (27) , while Western diets are animal-based and rich in red and processed meats (28) . It's giving us an opportunity to explore the association between relatively high levels of dietary copper intake and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The higher dietary copper intake may be related to the different dietary habits of adults in Western countries and China. Chinese Accepted manuscript diets tend to include large amounts of grains and legumes (26) , which are major sources of dietary copper (27) , while Western diets are animal-based and rich in red and processed meats (28) . It's giving us an opportunity to explore the association between relatively high levels of dietary copper intake and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…European and Middle Eastern countries have suboptimal selenium intake and status ( 33 ). China is a country of selenium deficiency, with an average selenium intake of 41.1 μg/day according to national surveys ( 34 ). It is estimated that 39–61% of Chinese residents' daily selenium intake is lower than the WHO/FAO recommendation (26–34 μg/day) ( 35 ), and the health problems caused by selenium deficiency in China needed special attention.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that those who had higher dietary intakes of copper and iron had a higher risk of T2DM, with the risk being more pronounced among those who were older, overweight, smokers, and who had a family history of diabetes [ 24 ]. In the second cohort study, Cui et al assessed the diet of 14,711 adults free of diabetes, with or without hypertension, and without any cardiovascular diseases in the China Health and Nutrition Survey and assessed the risk of those newly diagnosed with T2DM between 2000 and 2015 [ 25 ]. They found that the association between dietary copper and T2DM risk in healthy Chinese adults was not independent, but rather that copper was positively associated with a higher risk of developing T2DM, especially when selenium intake was lower than the medium ( p interaction = 0.0292) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the second cohort study, Cui et al assessed the diet of 14,711 adults free of diabetes, with or without hypertension, and without any cardiovascular diseases in the China Health and Nutrition Survey and assessed the risk of those newly diagnosed with T2DM between 2000 and 2015 [ 25 ]. They found that the association between dietary copper and T2DM risk in healthy Chinese adults was not independent, but rather that copper was positively associated with a higher risk of developing T2DM, especially when selenium intake was lower than the medium ( p interaction = 0.0292) [ 25 ]. The final cohort study by Laouali et al monitored 70,991 women with or without hypertension or hypercholesteremia for 20 years, examining the association between T2DM incidence and dietary copper-to-zinc ratio [ 26 ].…”
Section: Resultsmentioning
confidence: 99%